2018
DOI: 10.1111/jpc.13855
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of paediatric critical care asthma patients

Abstract: Intensive care length of stay (LOS) was unchanged over 12 years. Both invasive and NIV and IV magnesium sulphate use increased. LOS was directly related to the duration of IV β2-agonist. Asthma patients admitted to PICU typically have a brief stay and have a fairly predictable course. Prospective studies could explore the contribution of IV agents and the role of NIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
2
9
1
Order By: Relevance
“…Whilst asthma related PICU deaths in England (0.7%) were similar to those found in Australia (0.6%) and the Netherlands (0.6%) 17 , 18 , the reporting of asthma mortality in multi-centre PICU studies in the USA varied (0.3%, 1.9%, 4.3%) 19 , 21 , 30 . A UK study on general admissions in PICU using PICANet, found children who died in PICU stayed longer than who survived 31 , similar to our study.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Whilst asthma related PICU deaths in England (0.7%) were similar to those found in Australia (0.6%) and the Netherlands (0.6%) 17 , 18 , the reporting of asthma mortality in multi-centre PICU studies in the USA varied (0.3%, 1.9%, 4.3%) 19 , 21 , 30 . A UK study on general admissions in PICU using PICANet, found children who died in PICU stayed longer than who survived 31 , similar to our study.…”
Section: Discussionmentioning
confidence: 55%
“…Use of mechanical ventilation in children admitted to PICU in England (37.8%) is higher than that found in most other multi-centre reports from Australia (6–14%), the Netherlands (19%), while it varied in USA (19%, 3–47%) 17 , 18 , 21 , 46 . This may reflect a lower threshold for PICU admission in some countries, i.e.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…A study investigated outcomes of asthmatic patients admitted to the ICU revealed that the NIV use increased from 11 to 39% over 12 years. However, intubation rates remained similar despite increasing rates of NIV use (28).…”
Section: Asthmamentioning
confidence: 85%
“…Studies were excluded if they included patients with no clear diagnosis of asthma and patients over 18 years. All probabilities were contrasted with probabilities extracted from local studies to derivate the ranges in the sensibility analisis (8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Probabilitiesmentioning
confidence: 99%